Sustainable use of pumpkin: characterization of the pulp and valorization of by-products in obtaining preservative extracts - Leichtweis, Maria Gabriela (2023)
In the search for more sustainable industrial processes, the use of by-products from food production is an important strand [1]. Currently, the food industry has increasingly developed practical, ready-to-eat, and long shelf-life food products. How ever, this demand involves the use of synthetic food additives, which are associated with harmful effects on consumers health. Aiming to promote sustainability allied to the replacement of synthetic additives by natural alternatives, this work proposed the use of by-products from pumpkin processing, as a matrix for obtaining preservative compounds with potential to be applied in a product of pumpkin pulp. For that purpose, five different pumpkins cultivated in Egypt, namely ‘Butternut Squash’, ‘Golden Cushaw’, ‘Dickinson’, ‘Halloween’, and ‘Honey Delite’ were assessed. The pulp was evaluated regarding its nutritional value and chemical composition, in terms of free sugars (HPLC-RI), fatty acids (GC-FID), tocopherols (HPLC-FLD) and organic acids (UFLC-PDA). The by-products, more specifically the seeds, fibers, and peel, were evaluated for their antioxidant and antimicrobial capacity, as well as their cytotoxicity. All the pulp samples presented carbohydrates as the major compounds, followed by protein and fibers, with low content of fat. Regarding free sugars, fructose was predominant in all samples, except for the ‘Golden Cushaw’, which presented high levels of sucrose. Glucose was also present in high levels in most of the samples, and considerable contents of trehalose and raffinose were also found. Regarding fatty acids profile, the pulp revealed to be rich in saturated and polyunsaturated fatty acids, representing, respectively, about 40-50% of the total fatty acids, composed mainly by palmitic (C16:0), linoleic (C18:2n6c), α-linolenic (C18:3n3), and stearic (C18:0) acids. Regarding organic acids, all pulp samples presented malic and fumaric acids. In the samples that presented quinic acid, this was present in major quantity. Oxalic acid and traces of shikimic and citric acids were also detected. Also, the samples showed αand γisoforms of tocopherol, being the last one the most abundant. In addition to the rich nutritional composition of the pulps, as expected, the by-product extracts showed excellent preservative capacity. In the TBARS assay, the samples showed great capacity to inhibit lipid peroxidation, mainly the seeds and two of the five fibers. Moreover, all samples presented antibacterial capacity, inhibiting the growth of one to six of the eight tested bacteria. Also, some samples were capable of inhibiting the growth of the two fungal strains tested, with the peels standing out, protecting against at least three bacteria and one fungus. Additionally, none of the samples presented cytotoxic activity against the non-tumor porcine liver cells (up to 400 μg/mL), thus expressing its safety for food application. With this, it is possible to verify the potential use of pumpkin by-products as a source of natural preservatives, as well as the great nutritional value of the pulp, which can be further explored in the development of new pulp products preserved with their processing by-products. This favours a circular economy through sustainability.